Ambiguitas Bahasa Jawa dalam Wacana Humor di Desa Bendo Kecamatan Gondang Kabupaten Tulungagung - Riris Purbosari; Surana Surana (Universitas Negeri Surabaya, 2021)
Abstract Ambiguity is often found in humorous discourse. Ambiguity arises when the listener or reader has difficulty understanding the speech. Spoken language tends to often lead to ambiguity. Ambiguity is used to deceive the speech partner's mindset and misinterpret the meaning. This research uses several theoretical foundations, namely lexical semantics, grammatical semantics, ambiguity, pragmasemantics, things that determine linguistic meaning, and linguistic humor. This research is descriptive and includes qualitative research. The data collection procedure used is the listening method and the speaking method. Analysis of the data used is a pragmatic equivalent method. Based on the results of the research, there are three forms of ambiguity in Javanese language in humorous discourse in Bendo Village, Gondang District, Tulungagung Regency, namely phonetic ambiguity, lexical ambiguity, and grammatical ambiguity. There are five things that cause this ambiguity, namely homophones, homonyms, polysemy, grammatical word formation, and deviations from the maxim of cooperation in the way of implementation. The use of ambiguity is the result of human creativity. The breadth of language makes humans have the flexibility to process words to bring out humor. Keywords: Ambiguity, Discourse, Javanese Humor, Pragmasemantics. Abstrak Ambiguitas sering ditemukan dalam wacana humor. Ambiguitas muncul ketika pendengar atau pembaca sulit memahami tuturan. Bahasa lisan cenderung sering memunculkan ambiguitas. Ambiguitas digunakan untuk mengecoh pola pikir mitra tutur dan memelesetkan makna. Di dalam penelitian ini digunakan beberapa landasan teori, yaitu semantik leksikal, semantik gramatikal, ambiguitas, pragmasemantik, hal yang menentukan makna linguistik, dan humor linguistik. Penelitian ini bersifat deskriptif dan termasuk penelitian kualitatif. Tata cara pengumpulan data yang digunakan adalah metode simak dan metode cakap. Analisis data yang digunakan adalah metode padan pragmatis. Berdasarkan hasil penelitian, terdapat tiga bentuk ambiguitas bahasa Jawa dalam wacana humor di Desa Bendo Kecamatan Gondang Kabupaten Tulungagung, yaitu ambiguitas fonetik, ambiguitas leksikal, dan ambiguitas gramatikal. Terdapat lima hal yang menyebabkan ambiguitas tersebut, yaitu homofon, homonimi, polisemi, pembentukan kata secara gramatikal, dan penyimpangan maksim kerja sama cara pelaksanaan. Penggunaan ambiguitas merupakan hasil dari kreativitas manusia. Keluasan bahasa menjadikan manusia mempunyai kelonggaran mengolah kata untuk memunculkan humor. Kata Kunci: Ambiguitas, Wacana, Humor Jawa, Pragmasemantik.